Barriers to nutrition management among people living with HIV on antiretroviral therapy - Maertens, Julie A., author; Harman, Jennifer J., advisor; Chen, Peter, committee member; Stallones, Lorann, committee member; Harris, Mary, committee member; Dik, Bryan J. (Bryan Jay), committee member (Colorado State University. Libraries, 2011)
Human Immunodeficiency Virus (HIV) is a virus that attacks and impairs the body's natural defense system against disease and infection, in part through depletion of nutrients that are implicated in malnutrition and weight loss. Many nutritional problems among people living with HIV can be managed via nutrition intervention. No wide scale evaluation of HIV patient access or adherence to comprehensive nutrition intervention exists; however, there are potential barriers among patients to following nutrition advice from healthcare providers even when delivered. An online questionnaire among healthcare providers, along with focus groups and semi-structured interviews among patients living with HIV at three healthcare settings in Colorado were utilized in the current study in an effort to identify the barriers to nutrition management among people living with HIV. Healthcare providers reported being limited in the amount of nutrition intervention they could provide based on a lack of time and in-house referral services, and the co-occurrence of multiple illnesses among patients that demanded time and energy during appointments. Patients were limited in their ability to optimally manage their diet based on finances and transportation available for acquiring food, side effects associated with ARV (antiretroviral) medications, and their own cooking and meal planning skills. The nature of the barriers identified in the current study suggested a systems approach to optimizing nutrition management among HIV-positive patients may be an appropriate future direction of action.
Keywords: nutrition; HIV; phenomenology; providers; qualitative; patients